2018
DOI: 10.3390/molecules23112898
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Preliminary Structure and Antitumor Activity of Exopolysaccharide Produced by Streptococcus thermophilus CH9

Abstract: In the present study, the preliminary structure and in vitro antitumor activity of three exopolysaccharides (EPSs) from Streptococcus thermophilus CH9 were investigated. Then, three purified fractions of EPS-1a, EPS-2a, and EPS-3a were obtained by chromatography using DEAE-52 cellulose and Sephadex G-100, respectively. The average molecular weight of EPS-1a, EPS-2a, and EPS-3a, were 1.80 × 106, 1.06 × 106 and 1.05 × 106. The monosaccharide composition of EPS-3a was dramatically different from the others. The E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Furthermore, the inclusion of specific structures such as uronic acid, sulfate [56,57],βtype glycosidic linkages [57], protein molecules [58] and side chains [59] may influence the EPS' anticancer activity. The current EPSR3 contained no sulfate but uronic acid (28.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inclusion of specific structures such as uronic acid, sulfate [56,57],βtype glycosidic linkages [57], protein molecules [58] and side chains [59] may influence the EPS' anticancer activity. The current EPSR3 contained no sulfate but uronic acid (28.7%).…”
Section: Discussionmentioning
confidence: 99%
“…where they reported an anti-proliferative effect of crude and acidic EPS on HT-29 cells with the inhibition of the transition of G1 to S phase [ 26 ]. Naxin Sun, et al, found that the isolated fraction EPS-3a could stimulate HepG II cell apoptosis and cell cycle arrest at the G0/G1 phase by increasing incubation time [ 30 ]. Also Nehal M. El-Deeb, et al.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum peak height of rounded lumps was 55.7nm, the average roughness was 3.41 nm and the mean roughness was 1.48 nm. The maximum height of levan was much higher than the height of a single polysaccharide chain(0.1-1nm) suggesting that the tightly packed molecular structure formed in AFM images may be caused by the intermolecular and intramolecular aggregation of levan (Sun et al 2018). A similar result was reported for the EPS polymer from Lactobacillus sakei L3 (Wang et al 2019b) but different from Lactobacillus reuteri E81 glucan which had the tangled networks (İspirli et al 2019) and Mesona blumes gum EPS polymer which had an irregular shape like the worm (Tao et al 2008).…”
Section: Afm Analysismentioning
confidence: 92%
“…As observed by SEM images, levan in this study had a highly branched and porous structure. It was supposed that levan with a highly branched and porous structure was conducive to the formation of hydrated polymers and was most likely to be used in foods and cosmetics industries as texturing, thickening, stabilizing, and water-binding agent (Sun et al 2018;Yang et al 2018;Zhou et al 2018). Besides, SEM images indicated that levan had a sheet-like smooth and glossy surface, which had the potential to prepare plasticized lm (Feng et al 2018).…”
Section: Sem Analysismentioning
confidence: 99%